Do Bosses Get Bullied Too? A Qualitative Investigation of Causes, Impacts, and Treatments of Upward Workplace Bullying - Muhamad Farooq Rehan; Quaisar Ijaz Khan; Raheel Mumtaz (iRASD Journal of Management)
Workplace bullying is an emerging problem in the organizational setting, that if not properly managed can deteriorate the normal functioning of an organization and consequently may harm the achievements of organizational goals. Aim of this research study is to explore the causes, impacts, and treatments of upward workplace bullying where subordinate behave in an inhumane way against supervisor. Data was collected by using semi-structured interviews with 10 persons employed at senior supervisory levels in the city of Faisalabad, Pakistan. A thematic analysis indicates that unclear managerial boundaries, absurd job descriptions, and weak interpersonal skills of the employees are the major causes of upward bullying. Individual impacts of bullying on the aggrieved parties and organizational treatments to mitigate and control the phenomenon are discussed.